Firm selection and the role of union heterogeneity - Marco De Pinto; Jochen Michaelis (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
Empirical evidence suggests that high-productivity firms face stronger trade unions than low-productivity firms. Then a policy that puts all unions into a better bargaining position is no longer neutral for firm selection as in models with a uniform bargaining strength across firms. Using a Melitztype model, we show that firm selection becomes less severe. Since more low-productivity firms enter the market, the negative employment effect of unionization is mitigated. Neglecting inter-union differences in bargaining power leads to an overestimation of the negative labor market effects. However, trade liberalization increases unemployment because firms with the least powerful labor unions have to leave the market.
Keywords: F1; F16; J5; 330; Trade Unions; Bargaining Power; Firm Heterogeneity; International Trade; Unemployment